Improved analysis with spectral-domain optical coherence tomography angiography for evaluating vascular damage in exfoliation syndrome - Rongpei Zhang; Bingying Lin; Hairui Zhang; Yuncheng Ma; Na Xu; Ling Jin; Zhenyu Wang; Lei Tian; Munire Mohetaer; Aizezi Wumaier; Rongxin Chen; Danping Huang (Photodiagnosis and Photodynamic Therapy)
Purpose: To assess microvascular damage in exfoliation syndrome (XFS) patients with spectral-domain optical coherence tomography (OCT) and the correlations between OCT angiography (OCTA) parameters and systemic blood parameters in XFS. Methods: Twenty-one XFS eyes and 23 healthy eyes were included in this cross-sectional study. The foveal avascular zone (FAZ) area, vessel density (VD), thickness of the layers of the ganglion cell complex (GCC), homocysteine (Hcy) level, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were compared between the two groups. The correlations between OCTA parameters and systemic blood parameters were analyzed. Receiver operating characteristic curve analysis was performed to evaluate the ability of the OCTA parameters to predict XFS. Results: Compared with healthy controls, XFS patients had an enlarged FAZ area and a lower VD in the superficial vascular complex (SVC). The GCL thickness map and VD map of the SVC and deep vascular complex (DVC) revealed the presence of pathological damage at the outer superior (OS) and outer inferior (OI) sectors in XFS patients. In XFS patient, the FAZ area and OS VD of the SVC were strongly correlated with the Hcy levels, and the OS VD of the SVC was significantly negatively correlated with the NLR and PLR. The areas under the receiver operating characteristic curve for the SVC FAZ area and OS VD in predicting XFS were both >0.67. Conclusions: The pixel-level FAZ algorithm and VD map derived from OCTA can reflect microvascular damage in XFS. The fundus lesions observed in XFS are accompanied by systemic circulatory changes.